The Patrick Star show. Season 1, volume 2 [videorecording (DVD)]. (Nickelodeon, 2023)
Patrick Star continues to host a variety show from his room! Patrick's evil twin cousin shows up to ruin Patrick's reputation then when Patrick is injured his family members take turns hosting his show. Patrick's escapades take him to King Neptune's Palace, prison, and to The Starry Awards! This volume contains the second half of Season One, episodes 14-26, in a 2-disc set ₆ Plus The Tidal Zone: A SpongeBob Universe Special!